TEACHING AND LEARNING ENGLISH USING GOOGLE CLASSROOM AT SMK BUDISATRYA MEDAN DURING COVID-19 - Vera Marisa; Devi Widya Ningsih (PIONIR: JURNAL PENDIDIKAN, 2022)
The use of technology in teaching and learning process is inevitable. The Covid-19 pandemic has insisted the teaching learning process conducted online. Google Classroom is one of online learning platform used by teachers and students in SMK Budisatrya Medan. This study is aimed at describing the teaching and learning English by using Google Classroom at SMK Budisatrya Medan during Covid-19 pandemic. This study belongs to descriptive study. The participants in this study are all English teachers and students of SMK Budisatrya Medan. The result shows that teaching and learning English by using Google Classroom gives advantages for both teachers and students. The advantages are the ease of access, easy to operate, flexible time of teaching and learning, and supporting various learning sources. However, the teaching and learning using Google Classroom cannot be done optimally because of the lack of facilities experienced by some students and unsupportive communication feature of the application.